2021
DOI: 10.3390/diagnostics12010014
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Liver Fibrosis Predictors in Virologically Suppressed People Living with HIV without Hepatitis Virus Infection

Abstract: Severe liver fibrosis (LF) is associated with poor long-term liver-related outcomes in people living with HIV (PLWH). The study aimed to explore the prevalence and predictors of LF and the concordance between different non-invasive methods for the estimation of LF in HIV-infected individuals without hepatitis virus infection. We enrolled PLWH with HIV-1-RNA <50 copies/mL for >12 months, excluding individuals with viral hepatitis. LF was assessed by transient elastography (TE) (significant >6.65 kPa), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…In our study, the prevalence of liver fibrosis at the last visit in individuals with HIV mono-infection was of 8.1% using the APRI score and of 9% using the Fib-4 score, comparable with data from studies using non-invasive methods (20, 23,33,44). Additionally, the current study showed a significant increase of APRI and Fib-4 scores over time in this group with high CD4 T cell counts and relatively good real-life adherence to ART.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the prevalence of liver fibrosis at the last visit in individuals with HIV mono-infection was of 8.1% using the APRI score and of 9% using the Fib-4 score, comparable with data from studies using non-invasive methods (20, 23,33,44). Additionally, the current study showed a significant increase of APRI and Fib-4 scores over time in this group with high CD4 T cell counts and relatively good real-life adherence to ART.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, it is probable that similar to patients with chronic hepatitis B (53), distinct lower thresholds liver fibrosis are needed in PLWH on extensive ART. Sterling et al (34) have indicated lower optimal cut-offs for both APRI and Fib-4 scores in treated patients, while other authors have underlined the discordant results obtained using traditional APRI and Fib-4 cut-offs in PLWH without elevated transaminases (44). Nevertheless, considering the increase of the scores found over time in the cases with HIV mono-infection, a rigorous follow-up using at least serum-based scores should be considered in all PLWH on prolonged ART, irrespective on the presence of elevated transaminases or of other viral coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the plasma levels of the IFN-stimulated genes OAS1 and IP-10 were also significantly elevated in PLWH receiving cART compared with healthy individuals ( Figure 7, D and E ). Taken together, HIV/cART-induced pathogenic M2-macrophages and activation of IFN signaling may also play a role in increased risk of liver diseases reported in PLWH receiving ART ( 45 47 ).…”
Section: Resultsmentioning
confidence: 93%
“…ART has significantly improved the lifespan of PLWH. Because most drugs are metabolized by the liver, even low hepatotoxicity becomes an important clinical issue for PLWH with long-term cART ( 45 47 ). Therefore, monitoring PLWH with stable cART for potential emergence of liver injury and disease should continue to be of clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the full texts, a total of 36 studies met the inclusion criteria and were included in the final analysis ( 11 , 30–64 ) ( Figure 1 ). These studies were all from European countries, including the United Kingdom ( 42 , 46 ), France ( 31 , 35 , 38–40 , 64 ), Belgium ( 39 , 40 ), Greece ( 30 , 41 ), Italy ( 11 , 34 , 44 , 48 , 53 , 62 ), Spain ( 33 , 45 , 50 , 51 , 55 , 56 ), Denmark ( 36 ), Finland ( 37 , 57 ), Germany ( 32 , 39 , 40 , 43 , 49 , 58 , 63 ), Switzerland ( 54 ), Serbia ( 47 , 61 ), Austria ( 59 ), and Turkey ( 52 , 60 ) ( Supplementary Table S1 ). Most of the studies were cross-sectional in design, with a few prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%